Antibiofilm and Antivirulence Efficacies of Flavonoids and Curcumin Against Acinetobacter baumannii - Raorane, Chaitany Jayprakash; Lee, Jin-Hyung; Kim, Yong-Guy; Rajasekharan, Satish Kumar; García-Contreras, Rodolfo; Lee, Jintae (Frontiers in Microbiology, 2019)
Acinetobacter baumannii is well adapted to hospital environments, and the persistence of its chronic infections is mainly due to its ability of form biofilms resistant to conventional antibiotics and host immune systems. Hence, the inhibitions of biofilm formation and virulence characteristics provide other means of addressing infections. In this study, the antibiofilm activities of twelve flavonoids were initially investigated. Three most active flavonoids, namely, fisetin, phloretin, and curcumin, dose-dependently inhibited biofilm formation by a reference A. baumannii strain and by several clinical isolates, including four multidrug-resistant isolates. Furthermore, the antibiofilm activity of curcumin (the most active flavonoid) was greater than that of the well-known biofilm inhibitor gallium nitrate. Curcumin inhibited pellicle formation by and the surface motility of A. baumannii. Interestingly, curcumin also showed antibiofilm activity against Candida albicans and mixed cultures of C. albicans and A. baumannii. In silico molecular docking of the biofilm response regulator BfmR showed that flavonoid to BfmR binding efficacy was correlated with antibiofilm efficacy. In addition, curcumin treatment diminished A. baumannii virulence in an in vivo Caenorhabditis elegans model without cytotoxicity. The study shows curcumin and other flavonoids have potential for controlling biofilm formation by and the virulence of A. baumannii.